Hubungan Asupan Energi dan Aktivitas Fisik Dengan Status Gizi pada Remaja Putri di SMP Advent Bandar Lampung - Hutagalung, Wini Virginia Carissa; Adyas, Atikah; Dalimunthe, Nathasa Khalida (Journal of Education Technology Information Social Sciences and Health, 2025)
This study aims to analyze the relationship between energy intake and physical activity with nutritional status among adolescent girls at SMP Advent Bandar Lampung, using a quantitative method with a cross-sectional approach. The study population includes 140 female students from SMP Advent Bandar Lampung, with a sample of 114 respondents determined using the Slovin formula. The sample was taken proportionally and non-randomly from 7th grade (41 students), 8th grade (40 students), and 9th grade (33 students). Inclusion criteria were students who agreed to participate and signed a consent form, while exclusion criteria included students who were not attending school or were ill. Data were collected through a questionnaire on food consumption and physical activity, and BMI measurements using a digital scale and microtoise. Data collection was performed using a 2 x 24-hour recall and the International Physical Activity Questionnaire (IPAQ). Data were analyzed using SPSS software with steps including editing, coding, data entry, tabulating, and cleaning. Analysis included univariate analysis to describe the frequency of variables, and bivariate analysis using the Chi-Square Test to examine the relationship between independent and dependent variables. This study received ethical approval from the Research Ethics Committee of Universitas Mitra Indonesia. The results showed that 57.0% of the 114 students had good energy levels, 57.9% had good physical activity levels, and 61.4% had a healthy diet. There was a significant positive relationship between energy intake and nutritional status (p=0.000; p0.05), while no significant relationship was found between physical activity and nutritional status (p=0.602; p0.05)